The Psychometric Properties of Turkish Version of Autism Spectrum Screening Questionnaire in Children aged 6-18 years - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2016)
Objective: The objective of this study is to determine the psychometric properties of the Turkish version of the Autism Spectrum Screening Questionnaire (ASSQ-TR) and to find the best cutoff score for Pervasive Developmental Disorder (PDD) cases. Method: Children between 6 to 18 years old with diagnoses of PDD, Obsessive Compulsive Disorder (OCD), and Attention Deficit Hyperactivity Disorder (ADHD) were included. The healthy control (HC) group was recruited from children who did not have any psychiatric complaints or history. Furthermore, parents of 268 children filled the ASSQ-TR. Of the children, 51 were PDD, 67 were ADHD, 50 were OCD, and 100 were HC. In order to show the reliability of the ASSQ-TR, Cronbach's alpha values and test-retest were evaluated. ROC analyses was carried out to show concurrent validity and to determine the cutoff score. Results: The Cronbach's alpha of ASSQ-TR is 0,86, while the test retest reliability is r: 0,98. Total ASSQ-TR scores of children with PDD (27,96 +/- 9,5) were significantly higher than other groups (p<0,001). ROC analysis of ASSQ-TR showed the area under curve to be 0,97 with a cutoff of 16, having the maximum sensitivity (94,1%), specificity (89,0%), and 90,7% diagnostic accuracy of PDD versus HC scores. Conclusions: Our pilot data showed that ASSQ-TR is a reliable instrument that successfully differentiates clinically diagnosed PDD from HC. This instrument might therefore be useful for the screening of PDD in school-aged children in Turkish populations.
Keywords: Pervasive developmental disorders; Autism Spectrum Screening Questionnaire; reliability; validity; PERVASIVE DEVELOPMENTAL DISORDERS; HIGH-FUNCTIONING AUTISM; ASPERGER-SYNDROME; TOTAL POPULATION; ASSQ; RELIABILITY; VALIDITY; EPIDEMIOLOGY; VALIDATION; PHENOTYPE